Exploring Refinement Strategies for Single Housing of Male C57BL/6JRj Mice: Effect of Cage Divider on Stress-Related Behavior and Hypothalamic-Pituitary-Adrenal-Axis Activity - Buckinx, An; Van Schuerbeek, Andries; Bossuyt, Jo; Allaoui, Wissal; Van Den Herrewegen, Yana; Smolders, Ilse; De Bundel, Dimitri (Frontiers in Behavioral Neuroscience, 2021)
Introduction: Single housing of laboratory mice is often required to meet experimental needs, or to avoid intermale aggression. However, single housing is considered to negatively affect animal welfare and may compromise the scientific validity of experiments. The aim of this study was to investigate whether the use of a cage with a cage divider, which avoids physical contact between mice while maintaining sensory contact, may be a potential refinement strategy for experiments in which group housing of mice is not possible. Methods: Eight-week-old male C57BL/6JRj mice were single housed, pair housed or pair housed with a cage divider. Behavioral testing began after four (experiment 1) or ten (experiment 2) weeks in the given housing conditions. Exploratory activity, anxiety-like behavior and working memory were evaluated in the open field test, Y-maze spontaneous alternation test and elevated plus maze test respectively. Next, mice were subjected to an auditory fear conditioning task. At the end of the experiment the dexamethasone suppression test was performed to determine hypothalamic-pituitary-adrenal (HPA) axis responsiveness. Body weight was monitored throughout the experiment. Results: In experiment 1, mice housed with a cage divider had an increased distance traveled compared to pair housed mice without cage divider. In experiment 2, mice maintained with a cage divider had a significantly increased number of arm entries in the Y-maze spontaneous alternation test compared to single housed and pair housed mice. We found no other significant effect of housing conditions on body weight, exploratory activity, anxiety, working memory, fear memory processing or markers for HPA axis function in either experiment 1 or experiment 2. Conclusion: Overall, we did not observe long-term beneficial effects of pair housing with a cage divider. Moreover, our data show no negative impact of single housing compared to pair housing for a period of up to three months on exploratory activity, anxiety, working memory, fear memory processing or HPA axis responsiveness in male C57BL/6JRj mice.